An empirical analysis of research paradigms within international human resource management: The need for more diversity. (May 2020) - Kornau, Angela; Frerichs, Ilka Marie; Sieben, Barbara
The goal of this article is to provide a fine-grained analysis of international human resource management research that addresses the different perspectives applied in that research. We coded 203 peer-reviewed international human resource management articles published between 2011 and 2018 with content analytical methods guided by the compass of management research developed by Sieben, which is rooted in critical management research. We were particularly attentive to the various discursive orientations international human resource management scholars have adopted, including ideologically critical, poststructuralist, functionalist and interpretive perspectives. We further examined which methods, theoretical perspectives and topics were common within and across different perspectives. This analysis indicated that critical research intending to politicize and question existing structures and ways of organizing is still marginal. Along with the dominance of functionalist and interpretive studies, papers in our dataset commonly use a strategic human resource perspective, are predominantly interested in the human resource management–performance link and focus rather narrowly on multinational corporations and expatriates. Furthermore, while international human resource management scholars increasingly account for the contextual embeddedness of organizations through macro-level theories, they mainly apply institutional perspectives that view organizations as adapting to institutional constraints. We propose a more diverse and reflexive approach – inspired by ideologically critical and poststructuralist perspectives – that may help to overcome these blind spots. Such an approach might, for instance, look at types of organizations other than multinational corporations and individuals other than highly skilled expatriates and might explicitly bring multiple, external stakeholders into the picture. We conclude by suggesting that international human resource management research and practice would benefit from more research diversity which enables more holistic analyses of phenomena, more innovative research and resultant insights, and more space for meta-theoretical reflections.